Rusya Türkleri (tatar, başkurt, kırım tatarları) ve rus basınında II. meşrutiyet (1908-1909) - Demirbaş, İhsan (My University, 2009)
24 Temmuz 1908’de ilan edilen II. Meşrutiyet, sadece Osmanlı Devleti’nde değil bütün dünyada yankı uyandırmış, özellikle İslam aleminde büyük bir heyecana sebep olmuştur. Hem dini hem de ırki açıdan Osmanlı Türkleri ile kardeş olan Rusya Türkleri II. Meşrutiyet’in ilanı karşısında büyük bir heyecan duymuşlardır. Rusya Türkleri II. Meşrutiyet’in ilanını Avrupalılar tarafından parçalanması öngörülen Osmanlı Devleti’nin önce kendisini, daha sonra bütün İslam alemini yeniden canlandırmasının en önemli adımı olarak görmüşler, bütün Türklük ve İslam aleminin geleceği için ümitlenmişlerdir. Rusya Türkleri basınında II. Meşrutiyet’in ilanı ile Osmanlı Devleti’nde azınlıklara verilen hakların Rusya’dakinden çok daha geniş olduğunu belirtilmiş, Rusya Osmanlı Devleti’ni örnek almaya davet edilmiştir. Rusya’da 1905 İhtilali ile anayasal düzene geçilmesine rağmen 1907’de meydana gelen karşı devrimle hakların kısıtlanması ve bu sebeple hürriyet mücadelesinin devam etmesi, Rus kamuoyunun II. Meşrutiyet’i dikkatle izlemesine sebep olmuştur. Rusya’da Meşrutiyetin tam anlamıyla yerleşmesini arzulayan liberal Rus basını Osmanlı Devleti’ndeki hürriyetçi hareketi desteklerken, Çarlık taraftarı sağcı basın II. Meşrutiyet’in ilanının Çar’ın otoritesini sarsmasından endişelenerek, Osmanlı meşrutiyetçilerine muhalif bir tavır takınmıştır. Rusya Türkleri, Rus Basını, II. Meşrutiyet, Genç Türkler, Makedonya Sorunu

When the constitutional monarchy was restored by Sultan Abdulhamid II after the Young Turk Revolution (24 July 1908), it was not only had repercussions for Ottoman Empire but also in whole world, especially in İslamic world. Because of that historical situation Russia Turks who have brotherhood with Ottoman Turks as in view of both in religious and racial factors, were also so excited. Russia Turks had seemed this revolution as a survivor of the Ottoman Empire about whom the European powers planned to seperate into new states and they looked to this new regime was the most important step for resurrection of all İslamic world and became hopefull for the future of Turkic and İslamic world as well. With the begining of Second Constitutional Era in Ottoman Empire, Russia Turks announced in their press that Ottoman Turks had given more rights to minorities in their country than that of Russia and call upon the Russian goverment to take pattern of the Ottoman’s. The Counter Revolution in 1907 limited the rights which had been given by new constitutional order of 1905 Revolition thus the liberty struggle of the reformists had to continue in Russia and so Russian public opinion followed closely to the Young Turk Revolution of 1908. Liberal Russian press supported liberty movement in Ottoman Empire and wanted that properly constitutional monarchy must be set in Russia while conservative right-wing press who symphatized to Tsardom regime was anxious because of the Second Constitutional Era in Ottoman Empire and they opposed to Ottoman constitutionalists since they had conceived that Tsardom was shaken by the effect of this new wave. Key Words: Russia Turks, Russian Press, Constitutional Monarcy II, Young Turks, Macedonian Problem
Keywords: Genel Türk Tarihi; Rusya_Türkler; Tarih